PERHITUNGAN SUMBERDAYA TERUKUR BATUBARA DAN PERANCANGAN PIT PADA AREA PIT C PT. PIPIT MUTIARA JAYA (PT.PMJ) SITE BEBATU, DESA BEBATU KEBUN, KECAMATAN SESAYAP HILIR, KABUPATEN TANA TIDUNG, PROVINSI KALIMANTAN UTARA. - Dody Iswandi; Tamrin Kasim; Murad Murad (Departemen Teknik Pertambangan FT UNP, 2018)
PT. Pipit Mutiara Jaya is one of the companies engaged in mining, especiallycoal. The company is located in Bebatu Village, Sesayap downstream, Tana Tidung,North Kalimantan Province. PT. Pipit Mutiara Jaya is applying an open pit systemand is currently engaged in mining and exploration activities. The area explorationis called Pit CFG. After the company undertook detailed exploration activities thecompany has not conducted data processing to determine the quantity of measuredcoal resources, the value of stripping ratio, and the design pit at Pit C PT. PipitMutiara Jaya.Coal exploration was conducted on coal seam with research area + 24 ha.The information used in estimating the measured coal resource in the study areacame from 146 drill hole data and the mean distance between 50 meter drill holeswith the average depth of 60 meter borehole. Result of calculation of coal resourceby using method of polygon in mining software. Total of overburden is 12.488.344bcm which consist of amount of overburden, mud and the consecutive amount ofmix material is 3.309.185 bcm, 6.119.439 bcm and 3.059.719 bcm then total coaltonnage is 1.296 .445 tons consisting of 101B1 866.901 ton and 101H 429.544 tonsof seam and the stripping ratio is 1: 9,63.Keywords: exploration, coal, mine, drill, resource, polygon, overburden, seam,stripping ratio, pit